Karyotypic Diversity and Evolution in a Sympatric Assemblage of Neotropical Electric Knifefish - Cardoso, Adauto L.; Pieczarka, Julio C.; Crampton, William G. R.; Ready, Jonathan S.; de Figueiredo Ready, Wilsea M. B.; Waddell, Joseph C.; de Oliveira, Jonas A.; Nagamachi, Cleusa Y. (Frontiers in Genetics, 2018)
Chromosome changes can perform an important role in speciation by acting as post-zygotic reproductive barriers. The Neotropical electric fish genus Brachyhypopomus (Gymnotiformes, Hypopomidae) has 28 described species, but cytogenetic data are hitherto available only for four of them. To understand karyotype evolution and investigate the possible role of chromosome changes in the diversification of this genus, we describe here the karyotype of eight species of Brachyhypopomus from a sympatric assemblage in the central Amazon basin. We analysed cytogenetic data in the context of a phylogenetic reconstruction of the genus and known patterns of geographical distribution. We found a strong phylogenetic signal for chromosome number, and noted that sympatric species have exclusive karyotypes. Additional insights into the role of chromosome changes in the diversification of Brachyhypopomus are discussed.